Equalization transfers and the pattern of municipal spending: An investigation of the flypaper effect in Germany - Sebastian Langer; Artem Korzhenevych (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2018)
We investigate how lump-sum equalization transfers affect expenditures and taxes in the municipalities of the largest German state North Rhine-Westphalia. In general, those general-purpose transfers cannot be treated as exogenous variables. Thus, for the identification of causal effects, two exogenous adjustments in the transfer allocation formula are used as instrumental variables. Findings suggest the existence of the "flypaper effect" - municipalities use transfers to increase expenditures but do not reduce tax rates. Extra money from transfers is mainly used to finance social expenditures and public facilities. A set of robustness checks, including a spatial dependence model, confirm the results.
urn:nbn:de:bsz:14-qucosa-234984
Keywords: H21; H70; H71; H72; H77; 330; flypaper effect; local government expenditure; transfers; local taxation; Flypaper Effekt; Regionalregierung; Transfers; regionale Steuern